Pengaruh Penggunaan Aplikasi My Qur’an Digital Terhadap Intensitas Membaca Al-Qur’an Di Rumah Tahfizh Nurul Qur’an Parit 4 - Zulkarnainsyah, Zulkarnainsyah; Khairunnisa, Khairunnisa (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2024)
The problem in this study is due to the lack of educators, the digital Qur'an is one of the many learning media that is often used in the world of education today. With the existence of this digital Qur'an, it can help teaching staff in learning related to the Qur'an. This type of research is quantitative research. By using a simple regression formula. The respondents in this study were Santriwati Rumah Tahfizh Nurul Qur'an Parit 4  Data collection in this study used a questionnaire instrument. The results of data analysis through a questionnaire with the SPSS (Statistical Package For the Social Sciences) program showed that the results of the analysis: obtained Ftable 5.523 ≥ Fcal 5.32 Then it was accepted by Ha and rejected by Ho. So it can be concluded that there is a significant influence between the Use of the digital My Qur'an Application on the Intensity of Reading the Qur'an at Rumah Tahfizh Nurul Qur'an Parit 4.